Mudanças ambientais globais e geoindicadores - COLTRINARI, LYLIAN (Pesquisas em Geociências, 2001)
Global changes are modifications in the Earth System natural environment (physical, chemical, biological) as a consequence of interactions between atmosphere, oceans, cryosphere, and solid Earth, with the biota including humankind. These changes happen on a wide range of time scales, from years to hundreds of millions of years and they are significant features of Earth history. Geoindicators are measures of surface or near – surface geological processes and phenomena that vary significantly over periods of less than 100 years and that provide information meaningful for environmental assessment. They measure geological (mainly abiotic) variations that are important for understanding the terrestrial environment. There has been much interest on the subject of environmental monitoring of ecosystem dynamics and integrity but on the other hand it seems to be forgotten the search for indicators of natural processes and change in soils, landforms, surface, and groundwater that determine the character of the physical environment in general. Natural environmental changes in landscape features result from internal variations in geological and climatic parameters which lead to adjustments in surface processes and materials, and in vegetation. Anthropogenic activities act as external stresses that modify thresholds of stability and hamper understanding geoindicators changes. Procedures to quantify natural and man-made changes and to determine modifications in the recent past are proposed, with special reference to the Brazilian tropics.